An international review of local governance for climate change: implications for Hong Kong. Issue 1 (2nd January 2016) - Mah, Daphne Ngar-yin; Hills, Peter
Abstract : Cities have increasingly become the focal point for climate change initiatives. However, how cities respond to climate change challenges and through what mechanisms have remained largely unexplored. This paper develops a framework for local governance to examine and explain climate change initiatives in cities. Based on the analysis of 20 climate change initiatives in major cities and a detailed case study of Hong Kong, this paper has two main findings. First, local governments at the city level have an important role to play in climate change policies by embracing some key strategies (such as deliberation and partnership) and values (such as equity and legitimacy) of good governance. Second, by comparing and contrasting the experience in other cities, our case study of Hong Kong provides insights about the barriers that may limit a city's ability to adapt to new forms of governance that would enable it to better respond to climate change. The paper concludes by exploring the potential role of local governance as a model to strengthen climate change initiatives at the city level.